Audit of paediatric review in children less than 2 years with fracture, are we reviewing enough?. (24th May 2012) - Eltoum Elamin, F; Alam, M
Abstract : Aims: Fractures in children are the second most common presentation of child abuse. In younger children, especially in those less than 18 months, fractures should be considered suspicious of a non-accidental injury (NAI). Our objective was to identify whether children below the age of 24 months who presented to our hospital's Emergency Department (ED) and fracture clinic have been referred to or discussed with a Paediatrician prior to discharge from the hospital. Methods: A 1 year retrospective analysis was carried out of our ED and hospital notes from Oct 2009 to Sep 2010, of all children under the age of 24 months who presented with a fracture of any description to the ED and fracture clinic. The study looked at the gender, the type of fracture, whether the patient was reviewed by or discussed with paediatrician prior to discharge, outcome of review and whether social services or police were involved. Results: In 2009-2010 there was 41 children less than 2 years presenting with fracture. The largest percentage of fractures was long bone fracture (81%). Significant percentage (20% in <1 year old, 72% in 1 to 2 years old) have not been discussed with Paediatrician. 9 patients above 1 year of age were subsequently referred to social services and police (80% of the total referral). Conclusions: The authors believe that updating the current hospital guidelines to include children 1 to 2 years of age is essential to avoid missing fractures related to non-accidental injuries. This audit also highlighted that there is room for improvement in the documentation by the emergency department medical staff in relation to grade of doctor who initially saw the patient.